2014
DOI: 10.4103/0976-237x.132340
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated paracoccidioidomycosis diagnosis based on oral lesions

Abstract: Paracoccidioidomycosis (PCM) is a deep mycosis with primary lung manifestations that may present cutaneous and oral lesions. Oral lesions mimic other infectious diseases or even squamous cell carcinoma, clinically and microscopically. Sometimes, the dentist is the first to detect the disease, because lung lesions are asymptomatic, or even misdiagnosed. An unusual case of PCM with 5 months of evolution presenting pulmonary, oral, and cutaneous lesions that was diagnosed by the dentist based on oral lesions is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…According to gender and age we observed that PCM oral manifestations were more frequent in male patients, with 89.65% cases and age range of 41 to 62 years (75.85%), as it has been observed in earlier studies [5][6][7]. PCM oral manifestations occur at almost all ages, with highest incidence in ages between 30 and 50 years in its chronic form (adult type), which is the most common in 90% of the cases, with classic signs and symptoms that include pulmonary and mucosal involvement [5,6].…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…According to gender and age we observed that PCM oral manifestations were more frequent in male patients, with 89.65% cases and age range of 41 to 62 years (75.85%), as it has been observed in earlier studies [5][6][7]. PCM oral manifestations occur at almost all ages, with highest incidence in ages between 30 and 50 years in its chronic form (adult type), which is the most common in 90% of the cases, with classic signs and symptoms that include pulmonary and mucosal involvement [5,6].…”
Section: Discussionsupporting
confidence: 70%
“…In PCM, alcoholic habit was important in 31.03% of the cases, as previously described in Brazil [2,7]; whilst in cases of histoplasmosis only 5.5% of them were associated to such factor, similar to the findings described in Venezuela [1,11]. Other important risk factors for histoplasmosis are those related to fungal exposure by previous contact with bird or bat droppings: 38.88% of the cases involved such risk factor.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations